Thrombin activatable fibrinolysis inhibitor (TAFI) affects fibrinolysis in a plasminogen activator concentration-dependent manner - Guimarães, Ana H. C.; Rijken, Dingeman C. (Thrombosis and Haemostasis, 2004)
TAFIa was shown to attenuate fibrinolysis. In our in vitro study, we investigated how the inhibitory effect of TAFIa depended on the type and concentration of the plasminogen activator (PA). We measured PA-mediated lysis times of plasma clots under conditions of maximal TAFI activation by thrombin-thrombomodulin in the absence and presence of potato carboxypeptidase inhibitor. Seven different PAs were compared comprising both tPA-related (tPA, TNK-tPA, DSPA), bacterial PA-related (staphylokinase and APSAC) and urokinase-related (tcu-PA and k2tu-PA) PAs. The lysis times and the retardation factor were plotted against the PA concentration. The retardation factor plots were bell-shaped. At low PA concentrations, the retardation factor was low, probably due to the limited stability of TAFIa. At intermediate PA concentrations the retardation factor was maximal (3-6 depending on the PA), with TNK-tPA, APSAC and DSPA exhibiting the strongest effect. At high PA concentrations, the retardation factor was again low, possibly due to inactivation of TAFIa by plasmin or to a complete conversion of glu-plasminogen into lys-plasminogen. Using individual plasmas with a reduced plasmin inhibitor activity (plasmin inhibitor Enschede) the bell-shaped curve of the retardation factor shifted towards lower tPA and DSPA concentrations, but the height did not decrease. In conclusion, TAFIa delays the lysis of plasma clots mediated by all the plasminogen activators tested. This delay is dependent on the type and concentration of the plasminogen activator, but not on the fibrin specificity of the plasminogen activator. Furthermore, plasmin inhibitor does not play a significant role in the inhibition of plasma clot lysis by TAFI.
Keywords: TAFI; internal lysis; plasminogen activator; plasmin inhibitor